Upaya Polda Bali Dalam Meminimalisir Tindak Pidana Ujaran Kebencian Melalui Sosial Media - Jenny Iffanny Harahap; H. Nurianto Rahmand Soepadmo; Ida Bagus Anggapurana Pidada (PT FORMOSA CENDEKIA GLOBAL, 2022)
The legal regulations for the crime of hate speech have been regulated in the Criminal Code and also Law concerning information and electronic transactions. In this study using empirical juridical methods with interview qualitative techniques. This study aims to determine the efforts of the Bali Police in minimizing the crime of hate speech on social media The role of the Bali Police in dealing is carried out through preventive and repressive efforts. Preventive efforts are carried out by providing counseling to the public regarding the impact of the crime of hate speech on social media. Meanwhile, repressive efforts have been carried out, namely taking firm action against perpetrators of criminal acts based on legislation that regulates hate speech